Eksistensi Syaikh Mahfudz At-Tarmusi Dalam Studi Al-Qur’an: Sebuah Tinjauan Kitab Fath al-Khabir bi Syarh Miftah Al-Tafsir - Fatkhurrohman, Abdul Azis (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2023)
A figure's expertise places his status in a certain social position. This position becomes a keyword to identify the thoughts and ideas that are characterized. At the same time, this kind of identification contains a problem that leads to closed access to the mastery of other important ideas possessed by the figure. Shaykh Mahfudz, who is known by the keyword in the field of hadith sanad studies, experiences this problem. In this context, the author wants to examine the extent of the spread of Shaykh Mahfudz's ideas that are not much explored in the Qur'anic studies enclosure and what the implications are. Through internal and external relationships explored through Fath al-Khabir bi Syarhi Miftah at-Tafsir and looking at sociological relationships in the context of the spread of his knowledge. This research uses a qualitative method with a literature study approach. Through the book written by Shaykh Mahfudz; Fath al-Khabir bi Syarh Miftah at-Tafsir and other literature that supports this research. As a result, Shaykh Mahfudz with the depth of his Islamic knowledge horizons, he is not better known for his prominence in the field of Hadith studies than in Qur'anic studies. This confirms that the dissemination of knowledge within the framework of teacher and student relationships and the broad social context also influenced the burial of other important ideas owned by Shaykh Mahfudz.